2024
DOI: 10.3390/coatings14010095
|View full text |Cite
|
Sign up to set email alerts
|

Camelina sativa Oilseed Cake as a Potential Source of Biopolymer Films: A Chemometric Approach to Synthesis, Characterization, and Optimization

Danijela Šuput,
Lato Pezo,
Slađana Rakita
et al.

Abstract: In this work, the possibility of obtaining biopolymer films from Camelina sativa oilseed cake (CSoC) at different parameters of the synthesis process was investigated. The pH (values 8, 10, and 12), the temperature (60, 80, and 100 °C), and the concentration of the cake in the film-forming suspension (3, 4, and 5%) were varied. The films obtained were characterized by studying the mechanical, barrier, physico-chemical, structural, and biological properties (antioxidant and antimicrobial). The results showed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
(128 reference statements)
1
3
0
Order By: Relevance
“…The specific investigation conducted by Akharume et al [81] also revealed that storage time did have significant effects on microbial growth and reduction. Additionally, regarding the samples coated with CSoC biopolymer in the current study, we observed its inhibitory effect on microbial growth (Table 1), which is consistent with our previous research, in which Camelina sativa possessed antimicrobial properties [42]. The antimicrobial activity of Camelina sativa may be due to the presence of certain compounds, such as phenols, polyphenols, and glucosinolates, in camelina seeds, as reported before by [85].…”
Section: Storage Stabilitysupporting
confidence: 92%
See 3 more Smart Citations
“…The specific investigation conducted by Akharume et al [81] also revealed that storage time did have significant effects on microbial growth and reduction. Additionally, regarding the samples coated with CSoC biopolymer in the current study, we observed its inhibitory effect on microbial growth (Table 1), which is consistent with our previous research, in which Camelina sativa possessed antimicrobial properties [42]. The antimicrobial activity of Camelina sativa may be due to the presence of certain compounds, such as phenols, polyphenols, and glucosinolates, in camelina seeds, as reported before by [85].…”
Section: Storage Stabilitysupporting
confidence: 92%
“…Considering the complex system of highly valuable nutrients in both beetroot and sugar beet molasses, we applied a biopolymer coating synthesized from camelina cake (CSoC-based coating) to half of the samples to determine the effectiveness of the biofilm in preserving antioxidant activity and microbiological safety. Our previous research has confirmed that CSoC films have pronounced antioxidant and antimicrobial potential [42]. Therefore, we endeavored to ascertain whether these attributes persist when the CSoC coating is administered to a particular product.…”
Section: Storage Stabilitymentioning
confidence: 98%
See 2 more Smart Citations